2006
DOI: 10.1143/jjap.45.7311
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of BiFeO3 Thin Films by Reciprocal Space Mapping

Abstract: High-resolution X-ray diffraction reciprocal space mapping (HRXRD-RSM) was applied for the structural characterization of epitaxial BiFeO3 thin film grown on SrRuO3-coated (001) SrTiO3 single crystal substrate with a variety of film thicknesses ranging from 15 to 500 nm. Distinguishing monoclinic structure from rhombohedral or tetragonal structures was accomplished with a set of HRXRD-RSMs measured for several hkl diffraction conditions. The BiFeO3 thin films showed both monoclinic and tetragonal structures de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 28 publications
8
62
0
Order By: Relevance
“…Both our results and the results of previous works focusing on this R-phase (Ref. [25,26,27]) reveal similar lattice parameters and monoclinic distortions. RSM of the 001-diffraction condition of this film (Fig.…”
supporting
confidence: 88%
“…Both our results and the results of previous works focusing on this R-phase (Ref. [25,26,27]) reveal similar lattice parameters and monoclinic distortions. RSM of the 001-diffraction condition of this film (Fig.…”
supporting
confidence: 88%
“…An insulating band gap of 2.6 eV was obtained consistent with the range of band gaps (1.7-2.7 eV) obtained for bulk BFO. 43 The magnetic moment on Fe atom was found to be 4.13µ B close to the experimentally observed value of 3.75 µ B 65 and that on oxygen and bismuth was 0.04µ B and 0.004µ B respectively. The net magnetic moment per magnetic sublattice was found to be 3.96µ B .…”
Section: B Electronic and Magnetic Propertiessupporting
confidence: 77%
“…Due to thermal expansion and lattice mismatch between the BFO film and the substrates, different states of compressive or tensile strains can be generated by employing different substrates, resulting in different structural phases, from rhombohedral like monoclinic phase or tetragonal-like monoclinic phase, to a fully relaxed bulk like rhombohedral one. [30][31][32][33][34][35][36][37][38][39][40][41] One of the most promising findings is the prediction of a metastable state in strained BFO thin film with P4 mm symmetry. [42][43][44][45][46][47][48] Out of the variety of above reported phases, we considered the strain induced tetragonal (P4mm) (T) phase in BiFeO 3 (BFO) observed in thin films on an STO (001) substrate having the misfit strain ∼1.4% in our first principles study.…”
Section: Multiferroicsmentioning
confidence: 99%
“…In particular, ultra-thin BiFeO 3 films grown on (001) SrTiO 3 substrates with a SrRuO 3 buffer layer showed evidence for a transition to tetragonal symmetry. 11,18,19 Also, it has been reported that BiFeO 3 films grown on (001) SrTiO 3 can have a tetragonal structure with a giant c/a ratio, resulting from the higher strain induced by a Bi 2 O 3 layer, which can be formed between the film and the substrate. 20 In this paper, we report on the thickness dependence of the BiFeO 3 thin film structure in the ultra-thin regime under moderate compressive strain from (001) SrTiO 3 substrates.…”
mentioning
confidence: 99%